The construction of meaning in design-driven projects: a paradox initiated process. Issue 3 (3rd July 2019) - Knudsen, Line Sand; Haase, Louise Møller
ABSTRACT: In a world of ever-increasing products and services, companies are forced to think differently and find new approaches to bring meaningful and differentiating products to the market. In many cases, they have to go beyond the functional features in order to win the customers' hearts and attention. Design-driven innovation is acknowledged as a way to create new meaningful experiences to the users – not driven by market demands or technology development but by experience and the emotional parameters of the solution-to-be. Despite an increasing interest in design-driven innovation, the process of how new meanings are constructed is still a neglected area in existing design research. This paper explores how five Danish companies in diverse industries constructed new product meanings. The study indicates that 1) innovation of meaning starts from a paradox in an existing product-user relationship – often experienced by the designer 2) the central point for meanings' construction is the user's experience of the product, and 3) meaning is constructed in respect to a number of different product aspects including e.g. experience, interaction and expression.